PENGARUH KURS, INFLASI, DAN SUKU BUNGA TERHADAP HARGA SAHAM PADA PERUSAHAAN YANG GO PUBLIC DI BURSA EFEK INDONESIA TAHUN 2014-2016 (E-JRM : Elektronik Jurnal Riset Manajemen, 2017)
AbstrakDevelopment as contained in GBHN is one of the ways to increase national income. Toencourage national economic growth, the government continues to increase its investment. Oneway to get funds is in the capital market, which is the market for various long-term financialinstruments that can be traded, either in the form of debt or own capital, whether issued by thegovernment, public authorities, or private companies. In this research will be discussed about howthe effect of exchange rate, inflation and interest rates on stock prices. Because the research isexpected to be used by potential investors in making investment decisions. To consider investmentdecisions, comparable annual investment income with annual capital cost, which depends oninterest. The difference between annual income and annual cost is called an annual net income. Ifthe net annual net profit is positive, the investment is profitable, while if net profit is negative theninvestment is disadvantageous (Samuelson and Nordhaus, 1997: 138).Data collection in this study was conducted by literature study that is studying the literaturethat is deductive (theoretical) and other readings such as investor magazines, scientificpublications and scientific journals. Data Collection Technique is documentary that is collectingdata on Indonesia Stock Exchange in the form of JSX Statistic (yearly) during period 2014 untilSeptember 2016 at Investsi Gallery of Faculty of Economics (yearly).Keywords: Exchange Rate, Inflation, Interest Rate, Stock Price